2002
DOI: 10.1109/tpel.2002.805594
|View full text |Cite
|
Sign up to set email alerts
|

A novel maximum power point tracker for PV panels using switching frequency modulation

Abstract: A novel technique for efficiently extracting maximum power from photovoltaic (PV) panels is presented. The power conversion stage, which is connected between a PV panel and a load or bus, is a SEPIC or Cuk converter or their derived circuits operating in discontinuous inductor-current or capacitor-voltage mode. Method of locating the maximum power point (MPP) is based on injecting a small-signal sinusoidal perturbation into the switching frequency and comparing the ac component and the average value of the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(52 citation statements)
references
References 13 publications
0
49
0
3
Order By: Relevance
“…It can be seen that the optimal resistance for the photodiode becomes more selective at higher light intensities. Often a method known as maximum power point tracking (MPPT) is employed to ensure that the photodiode operates near the optimal load condition [23][24][25][26]. The optimum matching of photodiodes to resistive load has been previously outlined [23].…”
Section: Integrated Photodiodesmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the optimal resistance for the photodiode becomes more selective at higher light intensities. Often a method known as maximum power point tracking (MPPT) is employed to ensure that the photodiode operates near the optimal load condition [23][24][25][26]. The optimum matching of photodiodes to resistive load has been previously outlined [23].…”
Section: Integrated Photodiodesmentioning
confidence: 99%
“…The optimum matching of photodiodes to resistive load has been previously outlined [23]. Various techniques using switching regulators have also been proposed for tuning the photodiode for maximum power generation [24][25][26]. Each of these techniques requires additional energy overhead to carry out the MPPT algorithm.…”
Section: Integrated Photodiodesmentioning
confidence: 99%
“…There are two significant methodologies for power extraction; sun following the maximum power point (MPP) (Ts et al 2002). Solar amplifies the power, as illumination point influences the PV voltage-current (V-I) trademark significant to Kelly-cosine connection, yet it is not in the extent of this paper.…”
Section: Introductionmentioning
confidence: 96%
“…The power electronics interface is connected between a solar panel and a load or battery bus, is a pulse width modulated (PWM) DC-DC converter or their derived circuits is used to extract maximum power from solar PV panel [6]. I-V characteristic curve of photovoltaic (PV) generators based on various DC-DC converters [7][8][9][10] was proposed and concluded that SEPIC converter is the best alternative to track maximum power from PV panel.…”
Section: Introductionmentioning
confidence: 99%